2021
DOI: 10.1101/2021.07.14.21260544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Infectivity: Comparing Four PCR-based Assays to Detect Culturable SARS-CoV-2 in Clinical Samples

Abstract: With the COVID-19 pandemic caused by SARS-CoV-2 now in its second year, there remains an urgent need for diagnostic testing that can identify infected individuals, particularly those who harbor infectious virus. Various RT-PCR strategies have been proposed to identify specific viral RNA species that may predict the presence of infectious virus, including detection of transcriptional intermediates (e.g. subgenomic RNA [sgRNA]) and replicative intermediates (e.g. negative-strand RNA species). Using a novel prime… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…To minimize variation resulting from sample handling, we exclusively used samples that had been frozen within two days of sample collection from the patient. Once collected, clinical samples are routinely stored and transported at 4ºC and our previous work demonstrated that infectious virus and RNA are stable at both 4ºC and room temperature for over four days 23 . While limited residual material in clinical samples makes performing traditional plaque assays technically challenging, we have successfully used a focus forming assay performed in 96-well plates to measure infectious viral titer of volumes as small as 100-200 µl 23,24 .…”
Section: Main Textmentioning
confidence: 99%
See 4 more Smart Citations
“…To minimize variation resulting from sample handling, we exclusively used samples that had been frozen within two days of sample collection from the patient. Once collected, clinical samples are routinely stored and transported at 4ºC and our previous work demonstrated that infectious virus and RNA are stable at both 4ºC and room temperature for over four days 23 . While limited residual material in clinical samples makes performing traditional plaque assays technically challenging, we have successfully used a focus forming assay performed in 96-well plates to measure infectious viral titer of volumes as small as 100-200 µl 23,24 .…”
Section: Main Textmentioning
confidence: 99%
“…Once collected, clinical samples are routinely stored and transported at 4ºC and our previous work demonstrated that infectious virus and RNA are stable at both 4ºC and room temperature for over four days 23 . While limited residual material in clinical samples makes performing traditional plaque assays technically challenging, we have successfully used a focus forming assay performed in 96-well plates to measure infectious viral titer of volumes as small as 100-200 µl 23,24 . This approach enables us to measure individual infectious viral units directly from residual clinical samples, which to our knowledge are the first such measurements reported.…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations